2019
DOI: 10.3329/bjm.v35i1.39797
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy and Phytochemical Analysis of Three Aquatic Plant Species in Bangladesh

Abstract: Aquatic plants are generally considered as breeding grounds for mosquitoes and other harmful vectors of diseases. However, in recent years, some research has been carried out to test their significance as sources of antimicrobial lead molecules. The aim of this research was to study the phytochemical composition of local aquatic plant species and test their antimicrobial effect against selected bacterial strains. Three different aquatic plant samples were collected from a large water body near Dhaka. Ethanol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Water hyacinth (E. crassipes) contains many secondary metabolites. Hossain et.al [24] reported that the ethanol extract of water hyacinth leaves and stems contained alkaloids, saponins, steroidal compounds, flavonoids, phenolic compounds, glycosides, and cardiac glycosides. In addition, Kiristos et.al [25] also found tannins and terpenoids in the ethanol extract and methanol extract of water hyacinth leaves.…”
Section: Antibacterial Potential Of Water Hyacinth (Eichhornia Crassipes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Water hyacinth (E. crassipes) contains many secondary metabolites. Hossain et.al [24] reported that the ethanol extract of water hyacinth leaves and stems contained alkaloids, saponins, steroidal compounds, flavonoids, phenolic compounds, glycosides, and cardiac glycosides. In addition, Kiristos et.al [25] also found tannins and terpenoids in the ethanol extract and methanol extract of water hyacinth leaves.…”
Section: Antibacterial Potential Of Water Hyacinth (Eichhornia Crassipes)mentioning
confidence: 99%
“…With various secondary metabolite contents, water hyacinth has the potential to be used as antimicrobials that fight various disease-causing pathogens in shrimp and other pathogenic bacteria. Ethyl acetate extract of water hyacinth leaves and stems has been shown to inhibit growth of Staphylococcus aureus, and Salmonella typhi[24]. Water hyacinth leaf extract can inhibit the growth of Bacillus cereus (mtcc 6840), Streptococcus mutans (mtcc 497),…”
mentioning
confidence: 99%
“…The biomass of water hyacinth in Nigeria's aquatic environment has been estimated at between 28.8 and 32.2 tons of dry matter/hectare/year [ 25 ]. The ethanolic and methanolic extract of water hyacinth revealed the presence of the following compounds: alkaloids, flavonoids, phenols, carbohydrates, proteins, amino acids, tannins, terpenoids, saponins, and glycosides [ 26 28 ]. Furthermore, an analysis of the dried biomass of water hyacinth by Sivasankari and Ravindran [ 29 ] is as reported in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Water hyacinth comprises the following elements: C, O, Na, Mg, Al, Zn, K, Ca, Fe, P, and S, with carbon and oxygen having the highest percentages, making it a good source of biofuel for feedstock [ 32 , 33 ]. Other major elements were calcium (Ca), potassium (K), and silicon (Si) [ 28 ]. In the leaves, potassium and calcium were the most common elements present, while potassium, calcium, and chlorine were present in the stems in increased quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Water originated plants contain antimicrobial and phytochemical components like phenols, phycobiline, phenolic compounds, phlorotannins, acrylic acid, halo-genated ketones and alkanes, fatty acids,steroids, flavonoids, terpenoids, cyclic polysulphides, polysaccharide etc. (Abd El-Baky et al, 2008;Khan et al, 2014;Kavita et al, 2014;Hossain et al, 2018). Freshwater plants often are used for treating skin diseases and inflammation with potent antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%